Применение идей семи модулей на уроках в начальных классах - Зотова, С.Г. (My University, 2016)
Today more than ever interest of society in education and education of new generation increases. Education demands from teachers of big knowledge and huge return today. Now school and the teacher find the most effective ways to improve training process in order that the pupil was able to think, be critically independent, responsible, competent digital technologies. Enrichment of the content of education intellectual abilities and in the ways of creative activity passes through introduction of seven modules of the program. Training pupils, the teacher constantly has to be in search of such forms and methods which would allow to think productively, without fear to express them. Lessons have to be planned by the teacher well because such lessons conduct to successful result of trainees.
Keywords: effective ways; competent technologies; forms; methods; result